Local Culture-Based Learning in Improving Indonesian Literacy and Literature in Elementary Schools - Eliyanti, Ni Kadek; Septiani, Luh Enik; Juliatni, Ni Kadek Ena; Suryani, Komang; Kadu, Joko Godo; Sanjaya, Ida Bagus; Sudiana, I Nyoman (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
This research aims to investigate the implementation of local culture-based learning in elementary schools, with a focus on the use of mother tongue and regional cultural content in Buleleng Regency. Qualitative research methods were used to collect data through interviews, observations and document analysis of teachers from various levels of teaching experience. The research results show that most teachers recognize the importance of developing teaching materials related to local culture, although challenges are still found in the use of regional languages and the development of relevant learning media. The implications of this research show that the integration of local culture in the curriculum can increase student motivation and learning outcomes and strengthen cultural identity in the context of formal education. It is hoped that the results of this research can provide guidance for the development of education policies that are more inclusive and oriented towards local wisdom at the basic education level. Penelitian ini bertujuan untuk menginvestigasi implementasi pembelajaran berbasis budaya lokal di sekolah dasar, dengan fokus pada penggunaan bahasa Ibu dan muatan budaya daerah di Kabupaten Buleleng. Metode penelitian kualitatif digunakan untuk mengumpulkan data melalui wawancara, observasi, dan analisis dokumen terhadap guru-guru dari berbagai tingkatan pengalaman mengajar. Hasil penelitian menunjukkan bahwa sebagian besar guru mengakui pentingnya pengembangan bahan ajar yang berhubungan dengan budaya lokal, meskipun masih ditemukan tantangan dalam penggunaan bahasa daerah dan pengembangan media pembelajaran yang relevan. Implikasi dari penelitian ini menunjukkan bahwa integrasi budaya lokal dalam kurikulum dapat meningkatkan motivasi dan hasil belajar siswa serta memperkuat identitas budaya dalam konteks pendidikan formal. Diharapkan hasil penelitian ini dapat memberikan panduan bagi pengembangan kebijakan pendidikan yang lebih inklusif dan berorientasi pada kearifan lokal di tingkat pendidikan dasar.